Generalized Edema Caused by Albiglutide: A Case Report - Aziz, Kashif (Cureus, 2018)
Albiglutide is a long-acting glucagon‐like peptide‐1 (GLP-1) receptor agonist administered by weekly injection. Albiglutide-treated patients experience incidences of adverse effects, including cardiovascular, renal, and gastrointestinal symptoms and injection-site reactions. We report the first case of generalized edema induced by albiglutide. We present a 35-year-old female with type-2 diabetes. She developed generalized edema after the start of albiglutide. Her physical examination and all the laboratory tests, including thyroid function tests, albumin level test, and renal function test were unremarkable, and did not explain her generalized edema. Later on, her albiglutide was discontinued, which lead to the resolution of her edema. We conclude that her generalized edema could be due to a possible side effect of albiglutide.